The 11th hour [ turn mankind's darkest hour into its finest - Castleberry, Chuck; Conners, Nadia; DiCaprio, Leonardo; Gerber, Brian; Petersen, Leila Conners (Warner Home Video, 2008)
Explores the indelible footprint that humans have left on this planet, and the catastrophic effects of environmental neglect and abuse, and calls for restorative action through a reshaping of human activity